2005
DOI: 10.1080/13576500442000102
|View full text |Cite
|
Sign up to set email alerts
|

How preferred ear for listening moderates emotional cognitions in the prediction of personality

Abstract: Two studies investigate how cognitions of aurally presented information interact with aural preference (self-reported preferred ear for listening) in the prediction of personality. In Study 1, participants provided attractiveness cognitions of various statements after listening to aurally presented material. Aural preference x attractiveness interactions significantly predicted Extraversion and Neuroticism. In Study 2, participants provided cognitions of pleasantness from various scenarios. An aural preference… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 56 publications
1
16
0
Order By: Relevance
“…Although the evidence is not totally clear given the differences found between males and females, this study provides support for the argument 120 JACKSON that ear preference acts as a marker for contralateral hemispheric activity and supports the arguments of researchers who have previously made these claims (e.g., Dean & Reynolds, 1997;Kinsbourne, 1970; and more recently Jackson, 2005Jackson, , 2008Jackson et al, 2001). The link between ear preference and tympanic membrane temperature is useful to have identified, given that self-report ear preference is completely non-invasive and provides the opportunity to collect laterality information in the real-world environment or by means of questionnaire over the Internet.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…Although the evidence is not totally clear given the differences found between males and females, this study provides support for the argument 120 JACKSON that ear preference acts as a marker for contralateral hemispheric activity and supports the arguments of researchers who have previously made these claims (e.g., Dean & Reynolds, 1997;Kinsbourne, 1970; and more recently Jackson, 2005Jackson, , 2008Jackson et al, 2001). The link between ear preference and tympanic membrane temperature is useful to have identified, given that self-report ear preference is completely non-invasive and provides the opportunity to collect laterality information in the real-world environment or by means of questionnaire over the Internet.…”
Section: Discussionsupporting
confidence: 68%
“…Jackson (2008) reports that right ear preference people make shorter time estimates for how long it takes to undertake actions, and have less ''restraint'' compared to left ear preference people, and shows that disinhibition is greater among neurotic people with a right ear preference compared to left ear preference. Other recent evidence that ear preference is a potential measure of hemispheric asymmetry is also presented by Jackson (2005), who reports interactions with cognitions in the prediction of personality, and Jackson, Furnham, and Miller (2001), who report interactions with personality in the prediction of sales performance. It is therefore unsurprising that support for a relation between lateral preferences such as ear preference and hemispheric activity is ultimately supported by Dean and Reynolds (1997) and Kinsbourne (1970Kinsbourne ( , 1997.…”
Section: Tmt Diff and Ear Preferencementioning
confidence: 91%
See 1 more Smart Citation
“…This implied the network measures alone were not able to precisely predict the individual personality. There have been some studies trying to predict individual personality from subjects' social behaviors (Bai et al, 2012) or emotional cognition tasks (Jackson, 2005). These studies combined with our findings shed light on the future work of precise prediction of personality, and further suggested that to integrate the information of individual's outer behaviors and inner topological properties of resting-state functional brain networks may give new clues to the neuropsychology of personality dimensions.…”
Section: Discussionmentioning
confidence: 99%
“…Use of ear preference for this purpose is a straightforward and indirect way of measuring hemispheric asymmetry (Gullo, Jackson, & Dawe, 2010;Jackson, 2005, 2008, Jackson, 2010Jackson, Furnham, & Miller, 2001). Jackson (2008) demonstrates that ear preference is highly related to headset preference in telesales people, and provides evidence that ear preference is an index of action goal formation tendencies in specific support of Davidson's well-known model of laterality (e.g., Davidson & Sutton, 1995).…”
mentioning
confidence: 81%